Increasing the Resilience of British Columbia’s Rural Communities to Natural Disturbances and Climate Change - Krishnaswamy, Ajit; Simmons, Ellen; Joseph, Larry (Canadian Institute for Studies in Publishing Press, 2012)
It is predicted that climate change has increased the frequency and intensity of natural disturbances and weather related natural disasters. Rural forest-based communities are especially vulnerable to changes in natural disturbance regimes influenced by climate change because their economic, social, and cultural aspects of life are closely linked to the local environment and climate.In this article, we discuss the impacts of wildfires on communities as an example of how natural disturbances impact humans. The impacts to humans of wildfire is indicative of the type of effects that other natural disturbances such as widespread insect infestation, landslides, floods, drought, storms, avalanches, permafrost melt, forest diseases, erosion, and gradual ecosystem change can have on communities. First Nations communities may be significantly and uniquely impacted by natural disturbances and climate change due to their remote location, strong connection, and heavy reliance on the environment for subsistence and in preserving their culture and their unique and often vulnerable economic situation.We describe the uncertainty of predicting the frequency and intensity of natural disturbances in a particular location. We suggest that the most effective management response to address this uncertainty is to focus on reducing vulnerability and increasing community resilience. Finally, we list some of the management strategies and tools that communities and those that work with them have been using in British Columbia and elsewhere to increase community resilience to natural disturbances and climate change.